2004
DOI: 10.1002/bit.20130
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies on the aggregation of Aspergillus niger conidia

Abstract: Morphology has a crucial effect on productivity and the supply of substrate for cultures of filamentous fungi. However, cultivation parameters leading to the desired morphology are often chosen empirically as the mechanisms governing the processes involved are usually unknown. For coagulating microorganisms like Aspergillus niger the morphological development is considered to start with the aggregation of conidia right after inoculation. To elucidate the mechanism of this process, kinetic studies were carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 18 publications
3
70
1
9
Order By: Relevance
“…With q tip (μm h ) being a constant tip growth rate of n tip, the total hyphal length growth can be determined [52]:…”
Section: Microscopic Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…With q tip (μm h ) being a constant tip growth rate of n tip, the total hyphal length growth can be determined [52]:…”
Section: Microscopic Morphologymentioning
confidence: 99%
“…An essential relationship between tip growth and hyphal branching is described as hyphal growth unit (HGU), which is the average length of each tip in a mycelium [52]:…”
Section: Microscopic Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…In general, there is a strong connection between productivity and morphology of growing filamentous fungi (Grimm et al, 2005b). Previous studies have shown that the early stage spore aggregation is an important step in the morphological development of A. niger (Elmayergi et al, 1973;Galbraith and Smith, 1969;Grimm et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although the probe has already been utilized for offline characterization of microbial [95][96][97][98] and plant cell systems [99][100][101], applications in cell culture processes are not yet reported. The latest version of the G400 FBRM system distributed by Mettler-Toledo is fully autoclavable and therefore allows the integration of this technology even in cell culture processes.…”
Section: Focused Beam Reflectance Measurement (Fbrm)mentioning
confidence: 99%